Adjusted Survival Curves with Multivariable Laplace Regression. Issue 2 (March 2015) - Bellavia, Andrea; Bottai, Matteo; Discacciati, Andrea; Orsini, Nicola
Abstract : Supplemental Digital Content is available in the text.